Characteristics of Phytochemical Compounds and Anthocyanin of Extract from Purple Sweet Potato - Timur Ina, Putu; Diah Puspawati, G.A. Kadek; Ekawati, G.A; Ganda Putra, G.P. (Journal of Food Security and Agriculture, 2017)
Purple sweet potato is a tuber, that has a purple tuber flesh. This purple color can be used as a source of natural dyes in extract form. Purple sweet potato extract is a crude extract so apart extractable of dye component can also be extracted bioactive components such as other phytochemical compounds. The aim of this research was to determine the characteristics of phytochemical compounds and anthocyanins of purple sweet potato extract. The method of research used descriptive analysis to determine the type of phytochemical compounds and anthocyanins types. Purple sweet potato anthocyanin type done by ultra high performance liquid chromatography. The results showed the type of phytochemical compounds in the extract of purple sweet potato were saponins, alkaloids and flavonoids with quantity content such as: 7.99 ppm; 35.16 ppm and 182.28 ppm respectively. The types of anthocyanins were cyanidin 3-glucoside and peonidin 3- glucoside with quantity content such as: 24.43 ?g /ml and 13.26 ?g/ ml respectively